Determining the Dominant Cognitive Attitude toward the Environment among the Employees and their Intention to Adopt Ecological Behaviour - Abun, Damianus; Luna, Keith M.; Magallanes, Theogenia; Encarnacion, Mary Joy; Mansueto, Jecel M. (Technium Social Sciences Journal, 2021)
The study intended to find out the level of cognitive attitude toward the environment such as anthropocentric and eco-centric attitude toward the environment and ecological behaviour of employees and find out its correlation between attitude toward the environment and ecological behaviour of employees. To deepen and establish the theory of study, related literature was reviewed and carry out the study, the questionnaires were used to gather the data. The population of the study was all employees of the two colleges in the Ilocos region. The study used descriptive correlational research design and the Pearson r correlation was used to determine the correlation. The study found that the anthropocentric attitude is higher than the eco-centric attitude. Therefore the dominant attitude of employees toward the environment is an anthropocentric attitude. It is also found that there is a correlation between attitude toward the environment and ecological behaviour. Both environmental attitude affects the ecological behavior of the employees. Therefore, the hypothesis is accepted.